2014
DOI: 10.1017/s0031182013001224
|View full text |Cite
|
Sign up to set email alerts
|

Emerging paradigms in anti-infective drug design

Abstract: The need for new drugs to treat microbial infections is pressing. The great progress made in the middle part of the twentieth Century was followed by a period of relative inactivity as the medical needs relating to infectious disease in the wealthier nations receded. Growing realisation that anti-infectives are needed in many parts of the world, to treat neglected diseases as well as to combat the burgeoning risk of resistance to existing drugs, has galvanised a new wave of research into anti-microbial drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Here, we have shown that metagenomic approaches can document past infections. However, we have also recently shown that metagenomics can identify and characterize pathogens in contemporary samples 29 33 , so such approaches might soon also inform current and future infectious disease diagnosis and control.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that metagenomic approaches can document past infections. However, we have also recently shown that metagenomics can identify and characterize pathogens in contemporary samples 29 33 , so such approaches might soon also inform current and future infectious disease diagnosis and control.…”
Section: Discussionmentioning
confidence: 99%
“…Normally disease is self-limiting but the host may shed huge numbers of oocysts causing the infection to spread rapidly in calving areas and into the environment where they can remain infective for several years depending on environmental conditions. Livestock are well known as the main reservoirs for C. parvum [ 2 ] which is epidemiologically associated with zoonotic transmission [ 3 ] and are the species responsible for up to 50% of human cryptosporidiosis cases [ 4 ]. Infected neonatal calves tend to shed high concentrations of C. parvum oocysts [ 5 ] and in postcode sectors in Scotland which have a higher ratio of farms to humans, an increased rate of C. parvum infection in humans has been recorded [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ease of developing resistance to both components of the nifurtimox / eflornithine combination therapy (NECT, the newest treatment to enter the clinic) [ 10 ] is also a major concern [ 11 , 12 ]. Moreover, due to its status as a neglected disease of declining incidence, the current drug discovery pipeline for HAT is far from robust [ 13 ]. Thus, development of new drugs remains a critical task.…”
Section: Introductionmentioning
confidence: 99%